The association of dietary glutamine supplementation with the development of high salt-induced hypertension in rats - Yang, Liu; Xu, Longjin; Li, Juan; Wang, Huan; Sun, Jiahong; Yu, Ziqiang; Zhao, Xiaoqian; Zhao, Min; Xi, Bo (Frontiers in Nutrition, 2022)
Glutamine supplementation has been reported to affect blood pressure. However, its role in the progression of hypertension induced by high salt diet has not been elucidated. Male normotensive Wistar rats were exposed to high salt diet and treated with different doses of glutamine supplementation. Rats aged 6 weeks were assigned to 5 groups: 1) Normal-salt diet (0.3% NaCl, NSD); 2) High-salt diet (8% NaCl, HSD); 3) High-salt + low-dose diet (8% NaCl, 0.5 g of L-glutamine/kg body weight, HSLGD); 4) High-salt + middle-dose diet (8% NaCl, 1.5 g of L-glutamine/kg body weight, HSMGD); and 5) High-salt + high-dose diet (8% NaCl, 2.5 g of L-glutamine/kg body weight, HSHGD). After supplementing different doses of glutamine to male Wistar 6-week-old rats fed with HSD for 7 weeks, we found no difference in body weight among groups. Importantly, we showed that dietary L-glutamine supplementation could prevent the development of hypertension in a dose-dependent manner (dramatically lowering systolic blood pressure [SBP] and slightly reducing diastolic blood pressure [DBP] of hypertensive rats, while the differences of DBP between groups did not reach statistical significance). Our data further elucidated that dietary glutamine supplementation mildly alleviated the degree of left ventricular hypertrophy, including interventricular septal thickness (IVST) and left ventricular posterior wall thickness (LVPWT) in hypertensive rats. Together, our results offer evidence that the dietary uptake of glutamine may be associated with attenuating the development of high salt-induced hypertension and slightly alleviating the degree of left ventricular hypertrophy in hypertensive rats. Therefore, glutamine supplementation may act as a prospective dietary intervention for the treatment of hypertension.